Study of Employee Motivation and Performance by Focusing on the Work Environment and Laboratory Facilities at the Aviation Technology Center - Alhafidz, Fajri (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2023)
Employee motivation and performance are key factors in organizational success. In the context of aviation technology centers, where innovation and accuracy are top priorities, the role of work motivation and the quality of the work environment and laboratory facilities become very important. However, to date, research investigating the relationship between these factors in aviation technology centers has been limited. This study aims to explore the influence of the work environment and laboratory facilities on employee motivation and how this motivation impacts their performance at the Aviation Technology Center. With a better understanding of these factors, it is expected that organizations can take concrete steps to increase employee productivity and satisfaction. This research was designed using a descriptive method with a quantitative approach. The study used a saturated sampling technique contained in non-probability sampling, where the population in this study was 124 employees as engineers at the Center for Aviation Technology. The results of this study show that a comfortable work environment, adequate laboratory facilities, and high work motivation contribute significantly to the performance of employees at the Aviation Technology Center.